Paediatric handbook 2026-02-15T23:47:23+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... (Wiley-Blackwell, 2009)

(untitled)
* Provides information in an accessible style including clear illustrations. * Includes modern, community-based approaches. * Strong emphasis on the practical management by the doctor at first contact